The Effect of Curcuma zedoaria Extract on Enterococcus faecalis - Danica Anastasia; Aina Desmarani; Merryca Bellinda (Journal of Indonesian Dental Association, 2020)
Introduction: Enterococcus faecalis is a microorganism that is commonly found in persistent or secondary infection of root canal treatment. Irrigation is one of the main processes of endodontic triad to eliminate microorganisms in root canal infections. Curcuma zedoaria, a medicinal plant with antibacterial properties, is effective against several types of microorganisms and has the potential to be used as an alternative of chemical-based irrigant. Objective: This study aimed to evaluate the antibacterial activity of Curcuma zedoaria extract against Enterococcus faecalis. Methods: This in vitro study used C. zedoaria extract with six concentrations (100%, 90%, 80%, 70%, 60%, 50%) as tested groups, 2% Chlorhexidine and distilled water were used as a positive and negative control group, respectively. Solid Mueller-Hinton Agar (MHA) medium containing Enterococcus faecalis ATCC 29212 was perforated with a cork borer and dropped by 5 mL solution according to each group. The inhibition zone diameter was measured to evaluate antibacterial activity. Data were analyzed using a One Way ANOVA, continued by a Post-hoc Bonferroni. Results: The largest growth inhibition zone was associated with the highest concentration (100%), with a mean diameter of 8.36 mm. Conclusion: The 100% C. zedoaria extract concentration had the most effective antibacterial potency against E. faecalis.